Social capital and public policies for rural development. Analysis of the sowing life program - Blas-Cortés, Jonatan; Omaña-Silvestre, José Miguel; Quintero-Ramírez, Juan Manuel; Montiel-Batalla, Blanca Margarita (Revista Mexicana de Ciencias Agrícolas, 2023)
The objective of this research was to know the elements that determine the social capital in the beneficiaries of the Sowing Life Program, based on quantitative and qualitative information obtained from the beneficiaries. Two trust measures were used, with which three levels of trust were built: low, medium and high, and the proposed equations were estimated using a Probit model. The estimated models allow concluding that those beneficiaries surveyed who are older, inhabitants of rural populations and who voluntarily participate in local groups or organizations, have a greater probability of belonging to the groups of greater trust. Using the trust measure based on the perception of reliability of the people from the locality, the results of the model indicate that gender and ethnicity status have a negative and positive effect on trust level, respectively. While the model based on the rating given to different local actors suggests that these two characteristics have a negative effect on the level of trust. On the other hand, it was observed that, at higher levels of trust of the beneficiaries, their organizational performance through peasant learning communities increases.
Keywords: peasant learning communities; Probit model; trust